War and Adolescents: Factors Influencing Suicide Rates in Ukraine - Hura Андрій; Abdriakhimova Ціра (Psychosomatic Medicine and General Practice, 2025)
Relevance. The war in Ukraine creates a unique situation where adolescents are exposed to numerous stress factors, such as shelling, loss of loved ones, displacement, and the destruction of their usual way of life. These factors may have a cumulative effect on adolescents’ mental health and increase the risk of suicidal behavior. Studying the impact of war on the suicide rate among adolescents in Ukraine is crucial for understanding the scale of the problem and developing individualized approaches to support and intervention. Aim. To identify the factors affecting adolescents’ mental health and the causes of suicides among teenagers in Ukraine under martial law, using data from 2023 and 2024 on cases of children admitted to intensive and efferent therapy units, acute intoxications due to drug overdoses intended as suicide attempts. This study aims to determine key trends, risk factors, and potential causes of such incidents, as well as to assess the effectiveness of existing prevention and support measures for adolescents in crisis situations. Theoretical Approach. Cognitive Behavioral Therapy (CBT) is a scientifically validated method of psychotherapy based on identifying and modifying destructive cognitive schemas and behavioral patterns that contribute to the development of psycho-emotional disorders. Research shows that CBT effectively reduces anxiety and depression levels in adolescents, helps them develop emotional regulation skills, and fosters more adaptive behavioral strategies. The fundamental principle of CBT is that thoughts, emotions, and behaviors are interconnected, and changing destructive beliefs can contribute to improving mental well-being. This is particularly relevant for adolescents in crisis situations, as CBT teaches them to recognize and modify automatic negative thoughts that may provoke suicidal intentions. Materials and Methods. The following databases were used for the literature search: PubMed, APA PsychNet, Google Scholar, Scopus, and Web of Science. The keywords used for the search included: "suicidal behavior in adolescents," "cognitive behavioral therapy for PTSD," "war impact on adolescent mental health," "suicide prevention strategies," and "child and adolescent trauma in conflict zones." Inclusion criteria: Peer-reviewed articles published between 2015 and 2024, studies examining the psychological impact of war on adolescents, and research focusing on the application of Cognitive Behavioral Therapy for suicide prevention. Medical records of the Department of Intensive and Efferent Therapy, Acute Poisonings of the National Children’s Specialized Hospital "Okhmatdyt" of the Ministry of Health of Ukraine for 2023-2024. The study was conducted in compliance with all ethical norms and requirements, as well as with the consent of parents or guardians for data collection. The study included children who were admitted to the hospital due to medication poisoning with suicidal intent. For the main stage of the study, the following methods were used: "Hospital Anxiety and Depression Scale (HADS)," "Spielberger-Hanin Anxiety Scale," "Screen for Child Anxiety Related Emotional Disorders (SCARED)," and "Olweus Bullying Questionnaire (Olweus D. 2007)." Descriptive statistics were applied for data analysis. Results. The war creates additional psychological pressure on adolescents, which can manifest in various forms, such as fear, uncertainty, loss of loved ones, changes in their usual way of life, forced displacement, and more. These factors can contribute to the development and exacerbation of depressive states, which, in turn, increase the risk of suicidal behavior. In 2023 and 2024, an increase in the number of children with suicidal attempts and behaviors was observed. The main reasons for suicidal attempts were: Depressive state in 81.8% of cases. Disruptions in parent-child relationships in 40.9%. Bullying in 18.1%. Most of the children who sought help had overdosed on medication. In 2023, 40% of adolescents, and in 2024, 35% were under the supervision of a psychiatrist and psychologist and received pharmacological treatment. However, in many cases, parents did not monitor their children’s medication intake, which reduced the effectiveness of treatment. Additionally, most adolescents had comorbid conditions such as self-harming behavior, eating disorders, sleep and appetite disturbances, and asthenic conditions. In 2024, there was also an increase in repeated consultations for children and their parents, indicating a deepening of children’s psycho-emotional problems due to the ongoing war. Conclusion. The study results indicate a rising number of suicide attempts among adolescents in Ukraine, particularly linked to depressive states and bullying. Notably, in 2024, most suicide attempts were associated with depression, highlighting severe psycho-emotional issues among adolescents exacerbated by the war. Applying cognitive-behavioral therapy (CBT) as a framework for analyzing adolescents’ mental health provides deeper insights into the mechanisms of suicidal behavior formation. Medical records indicate that CBT contributed to a reduction in depressive symptoms in 73% of adolescents and a decrease in anxiety levels in 68% of study participants. Additionally, 59% of adolescents who completed a CBT course showed improvements in emotional regulation and a decrease in impulsive behavior. The obtained data emphasize the importance of developing comprehensive psychological support programs that incorporate cognitive-behavioral methods to address destructive beliefs and behavioral strategies in adolescents experiencing crises.